Towards time-resolved multi-property measurements by filtered Rayleigh scattering: diagnostic approach and verification - Doll, Ulrich; Kapulla, Ralf; Dues, Michael; Steinbock, Jonas; Melnikov, Sergey; Röhle, Ingo; Migliorini, Matteo; Zachos, Pavlos K. (Springer, 2023)
The use of multiple perspective views is a possible pathway towards the combined measurement of multiple time-resolved flow properties by filtered Rayleigh scattering (FRS). In this study, a six view observation concept is experimentally verified on a aspirated pipe flow. The concept was introduced in our previous work, and it has the ability to simultaneously measure high-accuracy time-averaged and time-resolved three-component velocity, pressure and temperature fields. To simulate time-resolution, multi-view FRS data at a single optimised excitation frequency are selected and processed for multiple flow properties. Time-averaged and quasi-time-resolved FRS results show very good agreement with differential pressure probe measurements and analytical temperature calculations and lie within ±2 m/s of complementary laser Doppler anemometry (LDA) velocity measurements for all operating points. The introduction of a multistage fitting procedure for the time-resolved analysis leads to a significant improvement of the precision by factors of 4 and 3 for temperature and axial velocity and 18 for pressure. Moreover, both processing methods show their capacity to resolve flow structures in a swirling flow configuration. It is demonstrated that the developed multi-view concept can be used to determine multiple flow variables from a single frequency measurement, opening the path towards time-resolved multi-parameter measurements by FRS.